Model Neural Membrane Droplet Interface Bilayers from Brain Total Lipid Extract for Studying Membrane-Peptide Interactions with Amyloid-β. Issue 1722 (12th May 2015) - Taylor, Graham J.; Sarles, Stephen A.
ABSTRACT: Droplet interface bilayers (DIBs) are formed using brain total lipid extract (BTLE) to create a synthetic bilayer whose lipid composition mimics that of neural cells. The electrical properties of BTLE DIBs, specifically membrane resistance, capacitance, and rupture potential, are determined and compared to the properties of bilayers formed using DPhPC, the most common lipid within the growing DIB field. There is no significant difference in the resistance or rupture potential of BTLE and DPhPC bilayers, for instance with average nominal resistance over 200 GΩ and rupture potential around 200 mV. In electrical measurements with either DPhPC or BTLE bilayers, applied voltages of up to ±150 mV yield low levels of leakage current. Upon interaction with the pore-forming amyloid-beta (Aβ) peptide, both bilayers display sudden significant voltage-dependent increases in conductance with characteristic threshold voltages well below 150 mV. Discrete single-channel type events are observed in the case of Aβ-BTLE whereas disordered fluctuating conductance is observed with Aβ-DPhPC. Circular dichroism is measured for Aβ incubated with BTLE and DPhPC liposomes, as well as pure Aβ, at a range of temperatures over a period of several weeks. Changes in secondary structure of liposome-bound and pure Aβ are significantly affected by both lipid type and temperature. A key finding includes the 100% conversion of Aβ to alpha-helical confirmation within 24 hours when incubated with liposomes (of either type) at physiologically relevant 37°C. The 100% alpha-helical Aβ is maintained for up to 2 weeks at 37°C when incubated with liposomes, although other structures begin to emerge after the 14 day mark. Between 14-31 days after reconstitution, Aβ incubated at 37C with BTLE bilayers displays longer lasting alpha-helical content than DPhPC. At the same temperature, pure Aβ is 100% alpha helical only at the 1 day mark with apparent restructuring from day 2 through day 31. Refrigerated Ab samples do not display 100% alpha-helical structure across the entire 31 day testing period. The differences observed between BTLE and DPhPC in both electrophysiological and spectroscopic experiments may be a result of phase separations or other variations in membrane fluidity that result from the use of a homogeneous total lipid extract. Time and temperature play essential roles in the aggregation and restructuring of potentially toxic Aβ oligomers, and there is motivation for further efforts to elicit the mechanistic differences in interactions of Ab with BTLE compared to DPhPC.